PENGARUH PDRB, PENGANGGURAN DAN INFLASI TERHADAP TINGKAT KEMISKINAN DI JAWA TIMUR TAHUN 2005-2014 (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2017)
Poverty is a problem that concerns many aspects as it relates to low income, illiteracy, low health status and inequality between sexes and poor environment (World Bank, 2004). The problem of East Java Province is not much different from the central government (national problem) that is, the high number of poverty and the increasing number of unemployment. This study examines the effect of GRDP, unemployment, and inflation on poverty level in East Java in 2005-2014. The purpose of this study is expected to analyze how and how big the influence of variables PDRB, unemployment and inflation to the level of poverty in East Java so that later it is expected to be used as one of the basic in termination of policy in overcoming poverty problem in East Java. The data used in this study is sekuder data obtained from the Central Bureau of Statistics (BPS) as well as browsing from the internet as a supporter. While the method of analysis used in this study is multiple linear regression analysis method with the help of SPSS. The results of this study indicate that the GRDP variable has positive and insignificant effect on poverty level, unemployment variable has positive and significant effect to poverty level, inflation variable has negative and insignificant effect to poverty level in east java.